Production and evaluation of an antiserum against envelope protein VP28 of white spot syndrome virus - Van Hau, Nguyen; Trong Tri, Do Nguyen; Thanh Nguyen, Le; Hong Linh, Le; My Trinh, Nguyen Thi (Vietnam Journal of Biotechnology, 2023)
Virus-associated white spot syndrome (WSSV) is one of the most popular diseases in shrimp, causing a huge economic loss globally  and also in Vietnam. Protein VP28 plays an important role in the initial steps of WSSV infection into shrimp cells. This protein binds to the shrimp cells as a viral adhesion molecule and then helps the virus enter the host cells. Therefore, many studies and applications related to the control of this virus have targeted VP28 as a potential antigen. To facilitate the study and application of VP28, this study focused on the development of a VP28-specific antiserum. The E. coli BL21(DE3)/pQE30-vp28 cells were cultured in LB medium supplemented with 100 µg/mL ampicillin and 0.5 mM IPTG was added to induce the expression of VP28. The cells were then disrupted by sonication and the supernatant fraction was used to purify VP28 using Ni-NTA affinity chromatography. The purified VP28 was injected into rabbits following a 90-day immunization protocol. The serum was then collected and validated for the ability to detect VP28 in Western Blot and ELISA. We found that the obtained antiserum could bind to both the recombinant and native VP28 in Western Blot assay. We also demonstrated that the antiserum could recognize VP28 in ELISA with the sensitivity of <0.39 ng/wells VP28 and the titer of 1/1,280,000. We successfully produced an anti-VP28 antiserum which can be used as a primary antibody in Western Blot and ELISA.